Realist evaluation of the Football Association's Post Graduate Diploma (PG Dip) in Coach Development. Issue 3 (24th March 2022) - Redgate, Sam; Potrac, Paul; Boocock, Emma; Dalkin, Sonia
ABSTRACT: Recent studies have provided important initial insights into the relational and micropolitical dimensions of coach educators' and coach developers' work. However, there remains a paucity of inquiry addressing how sporting organisations prepare these members of their workforce to achieve desired goals and objectives. This research uses realist evaluation and normalisation process theory to examine a bespoke 'reality grounded' learning initiative that targeted the professional judgements and decision making of experienced coach developers. This rigorous, longitudinal, and theoretically informed approach allowed for the generation of rich, causal, explanations of 'what has worked within this learning initiative, for whom, and under what circumstances'. Specifically, the study provides original and significant insights into the interconnections between (a) new ways of thinking, organising and acting, (b) already existing, socially patterned, knowledge and practices, and (c) positive and sustainable changes in everyday professional practice; something that has been largely absent in the wider coach education literature base to date. The research concludes that the programme entails more a transfer of knowledge from tutors to coach developers. Importantly, this intervention also aided (a) the development of a coach developer community, (b) facilitated the exchange of information and ideas between peers and, ultimately, (c) impacted on coach development practices and behaviours.